(untitled) (Research, Society and Development, 2020)
Introdution: It is suggested that the School of Postures programs can provide important effects in workers with musculoskeletal disorders. However, the lack of uniformity in the programs makes it difficult to analyze their real effects. Objective: To evaluate a Posture Schools program with a pedagogical-therapeutic focus on pain, flexibility and quality of life in workers with musculoskeletal dysfunction. Methodology: This is a quasi-experimental study composed of 24 workers with musculoskeletal dysfunction. The subjects received a protocol of 20 sessions (twice a week) that consisted of theoretical/educational classes, specific kinesiotherapy exercises and relaxation. The evaluated outcomes were pain, flexibility and quality of life. Pre- and post-treatment comparisons were performed using the Wilcoxon test, always considering a 5% significance level and a 95% confidence interval. Results and Discussions: There was an improvement in flexibility (p = 0.027), a decrease in the intensity of pain (p = 0.043) and an overall measure of quality of life (p = 0.043). Conclusion: The proposed School of Postures program was able to improve the outcomes assessed in the participating workers.